Interplay of thermal diffuse scattering and correlated compositional disorder in KCl1−xBrx - Schmidt, EM; Thomas, S; Bulled, J; Minelli, A; Goodwin, A (International Union of Crystallography, 2022)
Single-crystal X-ray diffuse scattering measurements are reported of the compositional series KCl1–xBrx, a model system for the broader family of disordered rocksalts. Using a combination of Monte Carlo simulations and attice dynamical calculations, we show that the observed diffuse scattering is well described in terms of (i) non-statistical anion distributions, (ii) local lattice relaxations accompanying Cl/Br substitution, and (iii) the contribution from low-energy phonons. It is found that a tendency for compositional domain formation broadens the thermal diffuse scattering by splitting and softening the acoustic phonon branches. This effect, which is strongest for intermediate compositions, is seen in both experiment and calculation alike. These results establish a link between local compositional order and unconventional lattice dynamics in this system, and reinforce emerging design principles of exploiting compositional fluctuations to tailor physical properties, such as thermal conductivity, that depend on phonon broadening.